The value of captive breeding programmes to field conservation: elephants as an example - Brandie Smith; Michael Hutchins (Pachyderm)
Even if reintroduction is not the goal of a captive breeding programme, zoos can contribute to wildlife and habitat conservation in a number of ways, including public education, scientific research, development and transfer of relevant technologies, professional training, political action and involvement in field conservation. The AZA Elephant SSP is an example of a programme where captive breeding and exhibition programmes can be of great value to in situ conservation both directly and indirectly. Examples of the value of public education, scientific research into reproductive biology, the testing of relevant technology and the training of veterinarian and biological support staff area discuss. Zoos can and do raise funds for field conservation. The authors end the paper by outlining cooperative ventures and information exchange between AZA and IUCN/SSC.